PERANCANGAN SISTEM PEMANTAUAN TEMPERATUR DAN KELEMBABAN RUANG RAWAT INAP PASIEN SECARA NIRKABEL DAN REALTIME - , RIZKA YULIANA; , Nazrul Effendy., ST., MT., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
According to ASHRAE (American Society of Heating, Refrigerating and Airconditioning Engineers), thermal comfort is a feeling when someone feels comfortable with the temperature state of the environment, which in the context of sensation described as a condition of person feeling neither too hot nor cold in a certain environment. Thermal comfort of patients in hospital is a support factor for the healing of patients. KepMenKes No. 1204/MenKes/SK/X/2004 sets the quality standard of air in the ward is at 22 ËC to 24 ËC with 45% to 60% humidity. A DHT11 sensor is used for detecting of temperature and humidity measurement. The sensor is connected to the microcontroller of Arduino and XBee as data sender for transmitting data through XBee router to XBee receiver which is connected to the microcontroller of Arduino. Then, the data will be displayed on a serial monitor of Arduino IDE (Integrated Development Environment) software. The testing of the monitoring system shows that by using the additional router, the XBee transmit distance is 66.5 m outdoor, 37.6 m indoor through 5 walls, and through 2 floors with the distance of 6.8 m.